Tea Tree Oil/Ethyl Cellulose Microcapsule Loaded Antimicrobial Textiles. Issue 2 (March 2020) - Beşen, Burcu Sancar
The aim of this experimental study was to obtain disposable antimicrobial cotton fabrics through applications of tea tree oil/ ethyl cellulose (TTO/EC) microcapsules. For this purpose, the TTO/EC microcapsules were prepared and characterized via scanning electron microscopy (SEM) and Fourier transform infrared-attenuated total reflectance (FTIR-ATR) analyses. The characterized microcapsules were then applied to 100% cotton fabric samples via the padding method and were investigated by FTIR-ATR and SEM analyses. In addition, the antibacterial activities of TTO, TTO/EC microcapsules, and fabric samples were also assessed against Escherichia coli and Staphylococcus aureus bacteria. The results showed that the microcapsules were successfully prepared and applied to the fabric samples. In addition, the targeted antimicrobial activities on the textile surfaces were achieved within acceptable levels.